Nano-antenna enhanced two-focus fluorescence correlation spectroscopy - Lutz Langguth (Nature Portfolio, 2017)
Abstract We propose two-focus fluorescence correlation spectroscopy (2fFCS) on basis of plasmonic nanoantennas that provide distinct hot spots that are individually addressable through polarization, yet lie within a single diffraction limited microscope focus. The importance of two-focus FCS is that a calibrated distance between foci provides an intrinsic calibration to derive diffusion constants from measured correlation times. Through electromagnetic modelling we analyze a geometry of perpendicular nanorods, and their inverse, i.e., nanoslits. While we find that nanorods are not suited for nano-antenna enhanced 2fFCS due to substantial background signal, a nanoslit geometry is expected to provide a di tinct cross-correlation between orthogonally polarized detection channels. Furthermore, by utilizing a periodic array of nanoslits instead of a single pair, the amplitude of the cross-correlation can be enhanced. To demonstrate this technique, we present a proof of principle experiment on the basis of a periodic array of nanoslits, applied to lipid diffusion in a supported lipid bilayer.